Concentração, operacionalização e rentabilidade bancária no Brasil pós-real - Barbosa, Flávia Félix (2016)
This dissertation is focused on the changes in concentration in operation and bank profitability in Brazil in the post-Real Plan period, specifically between 1994 and 2014. Therefore, discusses the importance of the Real Plan, financial liberalization and recent international financial crisis in large transformations which passed the Brazilian sector. The research guided in a theoretical and empirical approach, the light of post-Keynesian framework to demonstrate the evolution of concentration and operational structure, both on the side of active operations as the side of lending operations. The analysis and selected indicators shows that the banking sector lifted unprecedented concentration levels, while maintaining a net operating profile and highly profitable, despite the reduction of banking sector liquidity and profitability of private banks in the post-crisis period. This was possible mainly because of the restructuring proposed by the government and the Central Bank in the face of the difficulties of most of the banks with the introduction of the Real Plan in 1994 and after the international crisis started in 2007, and extremely dynamic behavior of the big banks.